DEVELOPMENT OF SCIENCE EXPERIMENTAL VIDEO WITH STEM-CRITICAL THINKING ASPECT: MAKING THERMOMETER FOR MEASURING THE GREENHOUSE EFFECT ON GLOBAL WARMING TOPIC - Indah Rahma Putri; Arief Muttaqiin (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
This research was motivated by the results of observations through interviews with science subject teachers at SMP Negeri 7 Padang. From the observation, experimental activities in the classroom were rarely carried out due to time constraints, so the research aims to develop a science experimental video with a STEM-critical thinking aspect: a thermometer for measuring the greenhouse effect on global warming topic. The type of research used is development research using the Plomp model which consists of 3 stages, namely preliminary research (initial investigation), prototyping stage (prototyping), and assessment phase (assessment stage). In this study, it was limited to the prototyping stage. The research instrument used was a questionnaire in the form of a validity and practicality sheet. The validity test was conducted on 3 expert validators and the practicality test was carried out on the seventh-grade students of SMP Negeri 7 Padang. The results of the validity test in the form of a validity sheet were obtained at 0, 91 with a very high validity category, while the practicality test carried out on students was found to be 93% with a very practical practicality category. Based on the data obtained, the science experimental video with STEM-critical thinking aspect: making thermometer for measuring the greenhouse effect on global warming topic very valid and very practical.